High-silicon low-carbon cement clinker prepared from waste incineration fly ash and preparation method of high-silicon low-carbon cement clinker
By using waste incineration of fly ash and other raw materials in cement clinker, the firing temperature of C4A3$ is reduced, so that it coexist with C5S2$ is solved, the problem of poor mineral stability is achieved, energy consumption reduction and performance improvement is achieved, and high performance is met and sustainable development needs.
Patent Information
- Application Number
- CN202411282178.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, C4A3$ and C5S2$ are difficult to coexist in the same clinker, resulting in high calcining temperature and poor mineral stability, affecting the medium-term mechanical properties of cement.
The raw materials such as waste incineration fly ash, desulfurization slag, iron trioxide and high-aluminum gangue are used to reduce the sintering temperature of C4A3$ through specific ratios and calcination procedures, so that it coexist with C5S2$ at 1200℃, and Improve mineral stability by grinding and cooling treatment.
It has achieved reduced energy consumption, reduced carbon emissions, and improved cement performance, overcome the problem of slow development of mechanical properties in the medium term, and effectively cured harmful heavy metals in fly ash, reducing environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a high-silicon low-carbon cement clinker from waste incineration fly ash and a preparation method thereof. Background Art
[0002] High-belite sulphoaluminate cement (BCSA) is a new type of low-carbon cement developed by reducing the C4A3$ (calcium sulphoaluminate) content and increasing the C2S (dicalcium silicate) content. However, BCSA still has some significant defects in its application. Although it reduces the dependence on high-grade aluminum raw materials and improves the hydration performance of cement to a certain extent, due to the mismatch of mineral activity, BCSA performs poorly in the development of medium-term mechanical properties. In particular, the hydration rate of C2S is slow, which causes the strength of BCSA to shrink in the later stage of hydration, making it difficult to meet the use requirements of actual projects.
[0003] In order to overcome these problems, it is necessary to develop a new high-silicon low-carbon cement clinker, Belite-Ye'elimite-Ternesite Cement (BYT for short). BYT is developed on the basis of BCSA by partially replacing C2S with C5S2$ (calcium sulfosilicate) as the main component. The thermal decomposition characteristics of C5S2$ make the firing temperature of BYT clinker generally about 250°C lower than that of ordinary Portland cement (PC) clinker and more than 100°C lower than that of sulfoaluminate cement (CSA) clinker. In addition, the low CaO content in BYT clinker leads to a significant reduction in CO2 emissions during its firing, showing significant low-carbon characteristics.
[0004] However, the biggest challenge in preparing cement containing C4A3$ and C5S2$ is that it is difficult for the two to coexist in the same clinker. The formation temperature ranges of C4A3$ and C5S2$ are 1200-1350°C and 1050-1200°C, respectively. During the formation of clinker minerals, C5S2$ is formed by the reaction of belite and anhydrite at 1050-1200°C, but when the calcination temperature is higher than 1250°C, C5S2$ will decompose into belite and anhydrite. This characteristic makes it difficult to obtain C4A3$ and C5S2$ at the same time during high-temperature calcination.
[0005] Therefore, how to ensure the stability and performance of minerals while reducing the calcination temperature has become a key issue in the research and development of BYT cement. Summary of the invention
[0006] The object of the present invention is to provide a high-silicon low-carbon cement clinker from waste incineration fly ash and a preparation method thereof, so as to solve the technical problem that C4A3$ and C5S2$ cannot coexist.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a high-silicon low-carbon cement clinker made of waste incineration fly ash, comprising the following raw materials in percentage by mass:
[0009] Waste incineration fly ash 25-30%, desulfurization slag 40-45%, ferric oxide 1-2%, high-alumina coal gangue 22-25%, gypsum 4-6%.
[0010] Preferably, in the above-mentioned waste incineration fly ash high-silicon low-carbon cement clinker, the mass fraction of calcium oxide in the waste incineration fly ash is 44.9%, the mass fraction of silicon dioxide is 5.11%, the mass fraction of aluminum oxide is 1.8%, the mass fraction of iron oxide is 2.03%, and the mass fraction of sulfur trioxide is 10.1%.
[0011] Preferably, in the above-mentioned waste incineration fly ash high-silicon low-carbon cement clinker, the mass fraction of calcium oxide in the desulfurization slag is 62.01%, the mass fraction of silicon dioxide is 6.70%, the mass fraction of aluminum oxide is 2.80%, the mass fraction of iron oxide is 19.50%, and the mass fraction of sulfur trioxide is 5.22%.
[0012] Preferably, in the above-mentioned waste incineration fly ash high-silicon low-carbon cement clinker, the mass fraction of calcium oxide in the high-aluminum coal gangue is 1.6%, the mass fraction of silicon dioxide is 30.22%, the mass fraction of aluminum oxide is 46.94%, the mass fraction of iron oxide is 3.65%, and the mass fraction of sulfur trioxide is 2.45%.
[0013] Preferably, in the above-mentioned waste incineration fly ash high-silicon low-carbon cement clinker, the mass fraction of calcium oxide in the gypsum is 33.99%, the mass fraction of silicon dioxide is 0.19%, the mass fraction of aluminum oxide is 0.03%, the mass fraction of iron oxide is 0.02%, and the mass fraction of sulfur trioxide is 44.00%.
[0014] The present invention also provides a method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash, comprising the following steps:
[0015] The waste incineration fly ash, desulfurization slag, ferric oxide, high-aluminum coal gangue and gypsum are mixed and ground to obtain a mixed powder;
[0016] The mixed powder is calcined and then cooled to obtain waste incineration fly ash high-silicon low-carbon cement clinker.
[0017] Preferably, in the above method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash, the particle size of the mixed powder is 70 to 90 μm.
[0018] Preferably, in the above-mentioned method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash, the calcination process is: calcining at 700°C for 20 minutes, heating to 1000°C for calcining for 20 minutes, and finally heating to 1250°C for calcining for 20 minutes.
[0019] Preferably, in the above method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash, the cooling rate is 30-50°C / min, and the final cooling temperature is 20-30°C.
[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention optimizes the cement raw material ratio and calcination system by utilizing the multiphase components (calcium sulfate) and other trace elements in the fly ash from garbage incineration, reduces the firing temperature of C4A3$, enables it to coexist with C5S2$ at 1200°C, and achieves the goals of reducing energy consumption and carbon emissions. The CaO content in BYT clinker is low, which greatly reduces the CO2 emissions in the production process. The chemical doping effect of the multiphase components and trace elements in the fly ash from garbage incineration improves the mineral lattice structure, increases the activity of C2S, overcomes the defect of BCSA in the slow development of medium-term mechanical properties, and improves the overall performance of cement. The use of effective ingredients in fly ash not only realizes the resource utilization and harmless treatment of fly ash, but also reduces the dependence on high-grade natural raw materials and reduces production costs. At the same time, harmful heavy metals and other pollutants in fly ash are effectively solidified, environmental pollution is reduced, economic and environmental benefits are significantly improved, and the demand for high performance and sustainable development of modern building materials is met. DETAILED DESCRIPTION
[0022] The present invention provides a high-silicon low-carbon cement clinker made of waste incineration fly ash, comprising the following raw materials in percentage by mass:
[0023] Waste incineration fly ash 25-30%, desulfurization slag 40-45%, ferric oxide 1-2%, high-alumina coal gangue 22-25%, gypsum 4-6%.
[0024] In the present invention, the mass percentage of the waste incineration fly ash is preferably 25-30%, more preferably 26.14-29.92%, and more preferably 29.8%.
[0025] In the present invention, the mass percentage of the desulfurized slag is preferably 40-45%, more preferably 42.26-44%, and more preferably 42.94%.
[0026] In the present invention, the mass percentage of the ferric oxide is preferably 1-2%, more preferably 1.24-1.75%, and more preferably 1.39%.
[0027] In the present invention, the mass percentage of the high-aluminum coal gangue is preferably 22-25%, more preferably 22.68-24.5%, and more preferably 23.17%.
[0028] In the present invention, the mass percentage of the gypsum is preferably 4-6%, more preferably 4.5-5.5%, and more preferably 5%.
[0029] In the present invention, the mass fraction of calcium oxide in the waste incineration fly ash is preferably 44.9%, the mass fraction of silicon dioxide is preferably 5.11%, the mass fraction of aluminum oxide is preferably 1.8%, the mass fraction of iron oxide is preferably 2.03%, the mass fraction of sulfur trioxide is preferably 10.1%, and other impurities are the remainder.
[0030] In the present invention, the mass fraction of calcium oxide in the desulfurization slag is preferably 62.01%, the mass fraction of silicon dioxide is preferably 6.70%, the mass fraction of aluminum oxide is preferably 2.80%, the mass fraction of iron oxide is preferably 19.50%, the mass fraction of sulfur trioxide is preferably 5.22%, and other impurities are the remainder.
[0031] In the present invention, the purity of ferric oxide is preferably 100%.
[0032] In the present invention, the mass fraction of calcium oxide in high-aluminum coal gangue is preferably 1.6%, the mass fraction of silicon dioxide is preferably 30.22%, the mass fraction of aluminum oxide is preferably 46.94%, the mass fraction of iron oxide is preferably 3.65%, the mass fraction of sulfur trioxide is preferably 2.45%, and other impurities are the remainder.
[0033] In the present invention, the mass fraction of calcium oxide in gypsum is preferably 33.99%, the mass fraction of silicon dioxide is preferably 0.19%, the mass fraction of aluminum oxide is preferably 0.03%, the mass fraction of iron oxide is preferably 0.02%, the mass fraction of sulfur trioxide is preferably 44.00%, and other impurities are the remainder.
[0034] The present invention also provides a method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash, comprising the following steps:
[0035] The waste incineration fly ash, desulfurization slag, ferric oxide, high-aluminum coal gangue and gypsum are mixed and ground to obtain a mixed powder;
[0036] The mixed powder is calcined and then cooled to obtain waste incineration fly ash high-silicon low-carbon cement clinker.
[0037] In the present invention, the pretreatment process of the waste incineration fly ash comprises the following steps: crushing to obtain, grinding particles, and then drying until the moisture content of the ground particles is less than 0.5%;
[0038] The particle size of the abrasive particles is preferably less than 15 mm, more preferably less than 0.75 mm, and more preferably 0.3 to 0.7 mm.
[0039] In the present invention, the pre-treatment process of the desulfurized slag, ferric oxide, high-aluminum coal gangue and gypsum is consistent with the pre-treatment process of waste incineration fly ash.
[0040] In the present invention, the particle size of the mixed powder is preferably 70 to 90 μm, more preferably 75 to 85 μm, and even more preferably 80 μm.
[0041] In the present invention, the calcination process is as follows: calcining at 700° C. for 20 min, heating to 1000° C. for 20 min, and finally heating to 1250° C. for 20 min.
[0042] In the present invention, the cooling rate is preferably 30-50°C / min, more preferably 35-45°C / min, more preferably 38-42°C / min; the final cooling temperature is preferably 20-30°C, more preferably 22-28°C, more preferably 24-25°C.
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] In the following examples, the mass fraction of calcium oxide in the waste incineration fly ash is 44.9%, the mass fraction of silicon dioxide is 5.11%, the mass fraction of aluminum oxide is 1.8%, the mass fraction of iron oxide is 2.03%, the mass fraction of sulfur trioxide is 10.1%, and the remainder is other impurities;
[0045] The mass fraction of calcium oxide in the desulfurization slag is 62.01%, the mass fraction of silicon dioxide is 6.70%, the mass fraction of aluminum oxide is 2.80%, the mass fraction of iron oxide is 19.50%, the mass fraction of sulfur trioxide is 5.22%, and the rest is other impurities;
[0046] The purity of ferric oxide is 100%;
[0047] The mass fraction of calcium oxide in high-aluminum coal gangue is 1.6%, the mass fraction of silicon dioxide is 30.22%, the mass fraction of aluminum oxide is 46.94%, the mass fraction of iron oxide is 3.65%, the mass fraction of sulfur trioxide is 2.45%, and the rest is other impurities;
[0048] The mass fraction of calcium oxide in gypsum is 33.99%, the mass fraction of silicon dioxide is 0.19%, the mass fraction of aluminum oxide is 0.03%, the mass fraction of iron oxide is 0.02%, the mass fraction of sulfur trioxide is 44.00%, and other impurities are the remainder.
[0049] Example 1
[0050] A high-silicon low-carbon cement clinker made from waste incineration fly ash comprises the following steps:
[0051] The waste incineration fly ash is crushed to obtain ground particles of the waste incineration fly ash, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated waste incineration fly ash;
[0052] The desulfurized slag is crushed to obtain ground particles of the desulfurized slag, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain the treated desulfurized slag;
[0053] The ferric oxide is crushed to obtain ground particles of ferric oxide, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated ferric oxide;
[0054] The high-aluminum coal gangue is crushed to obtain ground particles of the high-aluminum coal gangue, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content of the ground particles is less than 0.5%, thereby obtaining treated high-aluminum coal gangue;
[0055] The gypsum is crushed to obtain ground particles of gypsum, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated gypsum;
[0056] The treated waste incineration fly ash, the treated desulfurization slag, the treated ferric oxide, the treated high-aluminum coal gangue and the treated gypsum are mixed in mass percentages of 26.14%, 42.94%, 1.75%, 23.17% and 6% to obtain a mixed powder, and the mixed powder is ground in a wet ball mill until the particle size of the mixed powder reaches 80 μm; the powdered mixed powder is calcined at 700° C. for 20 min, heated to 1000° C. for 20 min, and finally heated to 1250° C. for 20 min; the calcined product is cooled to room temperature at a rate of 50° C. / min to obtain a waste incineration fly ash high-silicon low-carbon cement clinker.
[0057] Example 2
[0058] A high-silicon low-carbon cement clinker made from waste incineration fly ash comprises the following steps:
[0059] The waste incineration fly ash is crushed to obtain ground particles of the waste incineration fly ash, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated waste incineration fly ash;
[0060] The desulfurized slag is crushed to obtain ground particles of the desulfurized slag, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain the treated desulfurized slag;
[0061] The ferric oxide is crushed to obtain ground particles of ferric oxide, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated ferric oxide;
[0062] The high-aluminum coal gangue is crushed to obtain ground particles of the high-aluminum coal gangue, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content of the ground particles is less than 0.5%, thereby obtaining treated high-aluminum coal gangue;
[0063] The gypsum is crushed to obtain ground particles of gypsum, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated gypsum;
[0064] The treated waste incineration fly ash, the treated desulfurization slag, the treated ferric oxide, the treated high-aluminum coal gangue and the treated gypsum are mixed in mass percentages of 29.8%, 42.26%, 1.24%, 22.68% and 4.02% to obtain a mixed powder, and the mixed powder is ground in a wet ball mill until the particle size of the mixed powder reaches 80 μm; the powdered mixed powder is calcined at 700° C. for 20 min, heated to 1000° C. for 20 min, and finally heated to 1250° C. for 20 min; the calcined product is cooled to room temperature at a rate of 50° C. / min to obtain a waste incineration fly ash high-silicon low-carbon cement clinker.
[0065] Example 3
[0066] A high-silicon low-carbon cement clinker made from waste incineration fly ash comprises the following steps:
[0067] The waste incineration fly ash is crushed to obtain ground particles of the waste incineration fly ash, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated waste incineration fly ash;
[0068] The desulfurized slag is crushed to obtain ground particles of the desulfurized slag, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain the treated desulfurized slag;
[0069] The ferric oxide is crushed to obtain ground particles of ferric oxide, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated ferric oxide;
[0070] The high-aluminum coal gangue is crushed to obtain ground particles of the high-aluminum coal gangue, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content of the ground particles is less than 0.5%, thereby obtaining treated high-aluminum coal gangue;
[0071] The gypsum is crushed to obtain ground particles of gypsum, wherein the particle size of the ground particles is less than 0.75 mm; and then the ground particles are dried until the moisture content is less than 0.5% to obtain treated gypsum;
[0072] The treated waste incineration fly ash, the treated desulfurization slag, the treated ferric oxide, the treated high-aluminum coal gangue and the treated gypsum are mixed in mass percentages of 28.92%, 43.26%, 1.39%, 22.43% and 4% to obtain a mixed powder, and the mixed powder is ground in a wet ball mill until the particle size of the mixed powder reaches 80 μm; the powdered mixed powder is calcined at 700° C. for 20 min, heated to 1000° C. for 20 min, and finally heated to 1250° C. for 20 min; the calcined product is cooled to room temperature at a rate of 50° C. / min to obtain a waste incineration fly ash high-silicon low-carbon cement clinker.
[0073] The high-silicon low-carbon cement clinker from waste incineration fly ash prepared in Examples 1 to 3 was ground and passed through a 200-mesh sieve for quantitative analysis by XRD, and its phase composition was measured as shown in Table 1.
[0074] Table 1 Phase composition of high silicon low carbon cement clinker from waste incineration fly ash obtained in Examples 1 to 3
[0075] Phase type <![CDATA[C2S]]> <![CDATA[C4A3$]]> <![CDATA[C5S2$]]> <![CDATA[C4AF]]> C$ Example 1 48.1 29.1 12.4 8.3 2.1 Example 2 53.7 26.5 12.3 6.1 1.4 Example 3 52.3 28.8 10.7 6.7 1.5
[0076] The high silicon type low carbon cement clinker from waste incineration fly ash prepared in Examples 1 to 3 was ground to D 50 =40μm, cement paste was prepared with a water-binder ratio of 0.5, and standard curing was performed for 3 days, 7 days and 28 days. The compressive strength was measured and the results are shown in Table 2.
[0077] Table 2 Compressive strength of high silicon low carbon cement clinker from waste incineration fly ash obtained in Examples 1 to 3
[0078] 3-day compressive strength / MPa 7-day compressive strength / MPa 28-day compressive strength / MPa Example 1 25.6 38.1 45.6 Example 2 26.8 39.2 46.9 Example 3 28.2 40.5 47.5
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-silicon low-carbon cement clinker made from waste incineration fly ash, characterized in that: The preparation comprises the following raw materials in mass percentage: Waste incineration fly ash 25-30%, desulfurization slag 40-45%, ferric oxide 1-2%, high-alumina coal gangue 22-25%, gypsum 4-6%.
2. The high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 1, characterized in that: The mass fraction of calcium oxide in waste incineration fly ash is 44.9%, the mass fraction of silicon dioxide is 5.11%, the mass fraction of aluminum oxide is 1.8%, the mass fraction of iron oxide is 2.03%, and the mass fraction of sulfur trioxide is 10.1%.
3. The high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 2, characterized in that: The mass fraction of calcium oxide in the desulfurization slag is 62.01%, the mass fraction of silicon dioxide is 6.70%, the mass fraction of aluminum oxide is 2.80%, the mass fraction of iron oxide is 19.50%, and the mass fraction of sulfur trioxide is 5.22%.
4. The high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 3, characterized in that: The mass fraction of calcium oxide in high-alumina coal gangue is 1.6%, the mass fraction of silicon dioxide is 30.22%, the mass fraction of aluminum oxide is 46.94%, the mass fraction of iron oxide is 3.65%, and the mass fraction of sulfur trioxide is 2.45%.
5. The high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 3 or 4, characterized in that: The mass fraction of calcium oxide in gypsum is 33.99%, the mass fraction of silicon dioxide is 0.19%, the mass fraction of aluminum oxide is 0.03%, the mass fraction of iron oxide is 0.02%, and the mass fraction of sulfur trioxide is 44.00%.
6. The method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash according to any one of claims 1 to 5, characterized in that: The following steps are involved: The waste incineration fly ash, desulfurization slag, ferric oxide, high-aluminum coal gangue and gypsum are mixed and ground to obtain a mixed powder; The mixed powder is calcined and then cooled to obtain waste incineration fly ash high-silicon low-carbon cement clinker.
7. The method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 6, characterized in that: The particle size of the mixed powder is 70 to 90 μm.
8. The method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 7, characterized in that: The calcination process is as follows: calcining at 700° C. for 20 min, heating to 1000° C. for 20 min, and finally heating to 1250° C. for 20 min.
9. The method for preparing high-silicon low-carbon cement clinker from waste incineration fly ash according to claim 8, characterized in that: The cooling rate is 30-50°C / min, and the final cooling temperature is 20-30°C.
